New species and nomenclatural notes in Lobobrachus Sharp (Coleoptera, Carabidae, Pterostichini) - Campaner, Carlos; Will, Kipling W. (Papéis Avulsos de Zoologia, 2020)
A new species of Lobobrachus Sharp, 1885, Lobobrachus cleidecostae sp. nov., from Piauí state, Brazil, is described and illustrated. The genus and Lobobrachus lacerdae Sharp, 1885, are redescribed and the identity of L. alternans Tschitschérine, 1901, is discussed. Based on study of all available specimens and published descriptions it appears that L. alternans cannot be diagnosed and is a synonym of L. lacerdae. However, the syntypes of L. alternans cannot be located, thereby making a final decision on synonymy impossible to substantiate fully. Photographs of the aedeagi of L. lacerdae, L. cleidecostae, and specimens that best correspond to L. alternans, including those putatively identified by Tschitschérine, are presented for the first time.